Alterations in activin A–myostatin–follistatin system associate with disease activity in inflammatory myopathies. (28th January 2020) - Vernerová, Lucia; Horváthová, Veronika; Kropáčková, Tereza; Vokurková, Martina; Klein, Martin; Tomčík, Michal; Oreská, Sabína; Špiritović, Maja; Štorkánová, Hana; Heřmánková, Barbora; Kubínová, Kateřina; Kryštůfková, Olga; et al.
Abstract: Objectives: The aim of this study was to investigate the systemic and skeletal muscle levels of atrophy-associated myokines in patients with idiopathic inflammatory myopathies (IIM) and their association with clinical characteristics of myositis. Methods: A total of 94 IIM patients and 162 healthy controls were recruited. Of those, 20 IIM patients and 28 healthy controls underwent a muscle biopsy. Circulating concentrations of myostatin, follistatin, activin A and TGF-β1 were assessed by ELISA. The expression of myokines and associated genes involved in the myostatin signalling pathway in muscle tissue was determined by real-time PCR. Results: We report decreased levels of circulating myostatin (median 1817 vs 2659 pg/ml; P = 0.003) and increased follistatin (1319 vs 1055 pg/ml; P = 0.028) in IIM compared with healthy controls. Activin A levels were also higher in IIM (414 vs 309 pg/ml; P = 0.0005) compared with controls. Myostatin was negatively correlated to muscle disease activity assessed by physician on visual analogue scale (MDA) ( r = −0.289, P = 0.015) and positively to manual muscle testing of eight muscles ( r = 0.366, P = 0.002). On the other hand, follistatin correlated positively with MDA ( r = 0.235, P = 0.047). Gene expression analysis showed higher follistatin ( P = 0.003) and myostatin inhibitor follistatin-like 3 protein ( FSTL3 ) ( P = 0.008) and lower expression of activin receptor type 1B ( ALK4 ) ( P = 0.034), signal transducer SMAD3 ( P = 0.023) and atrophy marker atrogin-1 ( P = 0.0009) in IIM muscle tissue compared with controls. Conclusion: This study shows lower myostatin and higher follistatin levels in circulation and attenuated expression of myostatin pathway signalling components in skeletal muscle of patients with myositis, a newly emerging pattern of the activin A–myostatin–follistatin system in muscle wasting diseases.